2020
DOI: 10.1186/s13023-020-01556-9
|View full text |Cite
|
Sign up to set email alerts
|

Health technology assessment and reimbursement policy for oncology orphan drugs in Central and Eastern Europe

Abstract: Background The reimbursement of orphan drugs (OD) is an increasingly important for country policymakers, and still insufficiently understood, especially in Central and Eastern Europe. The aim of this research was to provide a comprehensive description of country-specific health technology assessment (HTA) policies as well as evaluate the percentage of HTA recommendations and reimbursement decisions for oncology OD. In addition, the study was designed to elucidate the impact of reimbursement of these drugs on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Such activities and growth rates in prices and expenditures for new medicines for oncology and orphan diseases are difficult to sustain under opportunity cost considerations within universal healthcare systems (Barrett et al, 2006;Godman et al, 2021g), necessitating a closer look at the most effective use of current resources. This is imperative with publications advocating greater spending on new medicines for cancer and orphan diseases in CEE countries despite limited health gain for most new cancer medicines (Cohen, 2017;Tomić et al, 2018;Cufer et al, 2020;Malinowski et al, 2020). The situation is different among LMICs, including sub-Saharan Africa, where in the case of patients with diabetes, key initial considerations include early diagnosis as well as availability and access to standard insulins (Godman et al, 2021b).…”
Section: Considerations In Choices For Funding Treatments Including I...mentioning
confidence: 99%
“…Such activities and growth rates in prices and expenditures for new medicines for oncology and orphan diseases are difficult to sustain under opportunity cost considerations within universal healthcare systems (Barrett et al, 2006;Godman et al, 2021g), necessitating a closer look at the most effective use of current resources. This is imperative with publications advocating greater spending on new medicines for cancer and orphan diseases in CEE countries despite limited health gain for most new cancer medicines (Cohen, 2017;Tomić et al, 2018;Cufer et al, 2020;Malinowski et al, 2020). The situation is different among LMICs, including sub-Saharan Africa, where in the case of patients with diabetes, key initial considerations include early diagnosis as well as availability and access to standard insulins (Godman et al, 2021b).…”
Section: Considerations In Choices For Funding Treatments Including I...mentioning
confidence: 99%
“…While lack of funding represents the major problem in the region, nascent HTA agencies are also a hindrance in some Central and Eastern European countries, such as Romania and Ukraine-these agencies have less health economic expertise to draw from than their Western European counterparts, which have long-running and experienced HTA bodies in place [such as the National Institute for Health and Care Excellence (NICE) in England, the Haute Autorite ´de sante ´(HAS) in France, and the Institut fu ¨r Qualita ¨t und Wirtschaftlichkeit im Gesundheitswesen (IQWiG) in Germany] [ [69][70][71][72]. Outdated and non-evidence-based eligibility criteria for novel therapies can prevent PwD receiving new, efficacious technologies, particularly if funding is instead diverted to medications at high prices with limited health gains [73][74][75][76]. It has been suggested that HTA implementation in the Central and Eastern European region be particularly resource-conscious, with transferability of evidence (e.g., clinical evidence, HTA methodology, and policy) between countries in the region emphasized wherever possible [77].…”
Section: Access and Fundingmentioning
confidence: 99%
“…Even though better access to medicines might be a shared goal amongst healthcare stakeholders, its achievement has proven complicated. In Europe, a plethora of evidence showcases variability in access to medicines across countries [3][4][5][6][7][8][9][10][11]. These variations can be attributed to a variety of factors: some are associated with broaderlevel features such as (i) the general country characteristics, including gross domestic product (GDP) per capita and the epidemiological profile; and (ii) the country's healthcare system characteristics, including healthcare expenditure, organisation of the healthcare system and clinical practices.…”
Section: Introductionmentioning
confidence: 99%